2021
DOI: 10.2196/24144
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Literacy and Beliefs About Medicines Among Taiwanese College Students: Cross-sectional Study

Abstract: Background Good eHealth literacy and correct beliefs about medicines are beneficial for making good health care decisions and may further influence an individual's quality of life. However, few studies have discussed these two factors simultaneously. Moreover, gender differences are associated with health literacy and beliefs about medicines. Therefore, it is important to examine the multiple relationships between college students’ eHealth literacy and beliefs about medicines, as well as gender dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Huang, C.L. et al showed that students with higher eHealth literacy had more positive views and beliefs about medication management [53]. Kyoung A Kim et al found that eHealth literacy was an important influence on self-efficacy when they investigated how type 2 diabetes patients understood and used online health information related to health promotion behavior [54].…”
Section: Indirect Effects Of Ehealth Literacy On Health Promotion Beh...mentioning
confidence: 99%
“…Huang, C.L. et al showed that students with higher eHealth literacy had more positive views and beliefs about medication management [53]. Kyoung A Kim et al found that eHealth literacy was an important influence on self-efficacy when they investigated how type 2 diabetes patients understood and used online health information related to health promotion behavior [54].…”
Section: Indirect Effects Of Ehealth Literacy On Health Promotion Beh...mentioning
confidence: 99%
“…According to the World Health Organization (WHO), eHealth can be defined as the application of the Internet and other related technologies in the healthcare industry to improve the access, efficiency, effectiveness, and quality of clinical and business processes utilized by healthcare organizations, practitioners, patients, and consumers to improve the health status of patients [3,4]. Ehealth literacy is the capacity to analyze health information obtained from electronic sources and apply what is learned to address or solve a health problem [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that e-health literacy is considered essential for improving healthcare delivery and quality of care as well as empowering caregivers and patients to influence control care decisions [2][3][4]6]. Although eHealth has the potential to revolutionize medical and public health practice, several organizational, cultural, and human resource reforms are still required for the widespread adoption of eHealth techniques for finding high-quality health information [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese college students had low eHealth literacy, and women were lower than men ( 8 ) . Under the condition of similar educational levels, Taiwan female college students had lower functional eHealth literacy than men ( 9 ) . There were also studies that reported women were associated with limited functional health literacy ( 10 ) , which may be due to their low educational level ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%